Nursing home placement in the Donepezil and Memantine in Moderate to Severe Alzheimer's Disease (DOMINO-AD) trial: secondary and post-hoc analyses. Issue 12 (December 2015) - Howard, Robert; McShane, Rupert; Lindesay, James; Ritchie, Craig; Baldwin, Ashley; Barber, Robert; Burns, Alistair; Dening, Tom; Findlay, David; Holmes, Clive; Jones, Robert; Jones, Roy; et al.
Summary: Background: Findings from observational studies have suggested a delay in nursing home placement with dementia drug treatment, but findings from a previous randomised trial of patients with mild-to-moderate Alzheimer's disease showed no effect. We investigated the effects of continuation or discontinuation of donepezil and starting of memantine on subsequent nursing home placement in patients with moderate-to-severe Alzheimer's disease. Methods: In the randomised, double-blind, placebo-controlled Donepezil and Memantine in Moderate to Severe Alzheimer's Disease (DOMINO-AD) trial, community-living patients with moderate-to-severe Alzheimer's disease (who had been prescribed donepezil continuously for at least 3 months at a dose of 10 mg for at least the previous 6 weeks and had a score of between 5 and 13 on the Standardised Mini-Mental State Examination) were recruited from 15 secondary care memory centres in England and Scotland and randomly allocated to continue donepezil 10 mg per day without memantine, discontinue donepezil without memantine, discontinue donepezil and start memantine 20 mg per day, or continue donepezil 10 mg per day and start memantine 20 mg per day, for 52 weeks. After 52 weeks, choice of treatment was left to participants and their physicians. Place of residence was recorded during the first 52 weeks of the trial and then every 26 weeks for a further 3 years. A secondary outcome of the trial, reported in this study, was nursing home placement: an irreversible move from independent accommodation to a residential caring facility. Analyses restricted to risk of placement in the first year of follow-up after the patients had completed the double-blind phase of the trial were post-hoc. The DOMINO-AD trial is registered with the ISRCTN Registry, number ISRCTN49545035. Findings: Between Feb 11, 2008, and March 5, 2010, 73 (25%) patients were randomly assigned to continue donepezil without memantine, 73 (25%) to discontinue donepezil without memantine, 76 (26%) to discontinue donepezil and start memantine, and 73 (25%) to continue donepezil and start memantine. 162 (55%) patients underwent nursing home placement within 4 years of randomisation, with similar numbers for all groups (36 [49%] in patients who continued donepezil without memantine, 42 [58%] who discontinued donepezil without memantine, 41 [54%] who discontinued donepezil and started memantine, and 43 [59%] who continued donepezil and started memantine). We noted significant (p=0·010) heterogeneity of treatment effect over time, with significantly more nursing home placements in the combined donepezil discontinuation groups during the first year (hazard ratio 2·09 [95% CI 1·29–3·39]) than in the combined donepezil continuation groups, and no difference during the next 3 years (0·89 [0·58–1·35]). We noted no effect of patients starting memantine compared with not starting memantine during the first year (0·92 [0·58–1·45]) or the next 3 years (1·23 [0·81–1·87]). Interpretation: Withdrawal of donepezil in patients with moderate-to-severe Alzheimer's disease increased the risk of nursing home placement during 12 months of treatment, but made no difference during the following 3 years of follow-up. Decisions to stop or continue donepezil treatment should be informed by potential risks of withdrawal, even if the perceived benefits of continued treatment are not clear. Funding: Medical Research Council and UK Alzheimer's Society.